Cognitive processes and reading skills in nursing students - Sánchez Trujillo, María de los Ángeles; Rodríguez Flores, Eduar Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
From a neuropsychological approach, the present study seeks to describe the cognitive operations applied during reading. This is a mixed case study, oriented to a sample of 200 Nursing students. For the collection of information, a test and a questionnaire of reading self-perception were applied to the students; as well as a semi-structured interview guide, aimed at teachers. It was found that they highlight that reading speed, memory and attention have an impact on the reading act, in addition to emotions and previous knowledge. In conclusion, cognitive operations are directly linked to the processes associated with reading.